Un análisis factorial para evaluar la pertinencia de un programa académico desde la perspectiva de los graduados: un estudio de caso (2020)
This article proposes two models to evaluate the pertinence of an academic program from the alumni’s perspectives. The first model is constructed by two factors or latent variables: i) alumni’s perception regarding the individual pertinence of the received education (that is, the perception of pertinence in personal, work and professional development levels) and ii) alumni´s perception regarding the social pertinence of the received education. Similarly, the second model is built by two factors or latent variables regarding alumni’s competencies: i) the perception of their level of instrumental competencies and ii) the perception of their level of systemic competencies. The construction of these models was carried out in two phases: fi rst an exploratory factor analysis, which was followed by a confi rmatory factor analysis. Results demonstrate the pertinence of the program.